STUDI DESKRIPTIF KEJADIAN MALARIA DI PUSKESMAS II SUMPIUH KABUPATEN BANYUMAS TAHUN 2010-2011 - Wijayanti, Siwi Pramatama Mars; Gamelia, Elviera (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2012)
ABSTRACT   Continuing the Malaria cases in Primary health Care II Sumpiuh rise a problem every year. The aims of this research was to find out the description of malaria cases based on people, place and time in primary helath care II Sumpiuh during 2010 and 2011. This research was descriptive, and sample was all of the population. Data obtained by took secondary data from primary helath care II Sumpiuh and then analysed by univariat. The result of this research showed that 106 people (33.44% from the sample identified), and in 2011 until April, 17 people (11.26% from sample identified) were infected by Malaria. Man more have a risk to get malaria, because from the result showed that the number of patient of Malaria is more in man that women. Group of age which showed the highest number of positive malaria is 30-45 yearsold in 2010 and between 45-60 yearsold in 2011. Banjarpanepen is the village which has a highest number of malaria cases comparing with other village in primary health care II Sumpiuh. Suggestion from this result is the need of complete data, regarding the location of patient, type of plasmodium which infected, and also the surveillance of Malaria must be regularly and active to decrese the number of malaria cases.   Kata Kunci : Malaria, Plasmodium, Epidemiology, Deskripsi Jurnal Kesmasindo  Volume 5( 1)  Januari 2012,  hlm. 75-87